Quality of Sleep in the Cypriot Population and Its Association With Multimorbidity: A Cross-Sectional Study - Kyprianidou, Maria; Panagiotakos, Demosthenes; Kambanaros, Maria; Makris, Konstantinos C.; Christophi, Costas A. (Frontiers in Public Health, 2021)
Poor sleep is a relatively common condition with possibly serious adverse health consequences. Lack of sleep affects the endocrine, immune and nervous systems. In Cyprus, there is no information about the quality of sleep in the population. The goal of this study was to assess the quality of sleep in the Cypriot population and evaluate its association with multimorbidity. A representative sample of the adult population of Cyprus was selected in 2018-2019 among the five government-controlled municipalities of the Republic of Cyprus using stratified sampling. Data on sleep quality as well as on the presence of chronic, clinical, and mental health conditions were collected using a validated questionnaire. Diseases were classified according to the International Classification of Diseases, 10th Revision (ICD-10). A total of 1140 Cypriot men and women over 18-years old (range: 18-94) participated in the study. The median Pittsburgh Sleep Quality (PSQI) score of the participants was 5 (first quartile=3, third quartile=7) with the maximum score being 17, which suggests that the Cypriot population has a relatively good quality of sleep overall, although, almost one third of the study population had a poor quality of sleep. Females, residents of Paphos, and married people had a poorer quality of sleep (p<0.05). Having a poor quality of sleep was associated with higher odds of multimorbidity (OR=2.21, 95% CI: 1.55, 3.16), even after adjusting for demographics, socioeconomic and lifestyle factors. Adopting good sleep habits, could be beneficial and would potentially help reduce the risk of multimorbidity. Public health guidelines regarding the importance of sleep and its association with multimorbidity should be considered.